Thieves - Bryon, Lucie (Nobrow, 2022)
What happened last night? Ella can't seem to remember a single thing from the party the night before at a mysterious stranger's mansion, and she sure as heck doesn't know why she's woken up in her bed surrounded by a magpie's nest of objects that aren't her own. And she can't stop thinking about her huge crush on Madeleine, who she definitely can't tell about her sudden penchant for kleptomania... But does Maddy have secrets of her own? Can they piece together that night between them and fix the mess of their chaotic personal lives in time to form a normal, teenage relationship? That would be nice.